Influence of patients’ rights charter on health systems responsiveness in selected counties in Kenya: health care provider perspective - Njuguna, Susan; Mwaura Tenambergen, Wanja; Mapesa, Job (International Journal Of Community Medicine And Public Health, 2019)
Background: The role of health care providers in the implementation of responsiveness of health systems is unclear. Responsiveness of health systems is one of the goals set out by WHO in 2000. Effective leadership and governance of health systems incorporates all players involved in policy implementation. The objectives of the study were to establish how the health care provider’s awareness of patients’ rights charter influence health systems responsiveness and to establish how the health care provider practice of patients’ rights charter influence responsiveness of health systems in primary care settings. Methods: This was an exploratory cross section descriptive study design that used a psychometric semi- structured questionnaire to collect qualitative data that was analyzed quantitatively. Respondents were 62 purposively sampled health care providers from four, primary care health facilities. Key informant interviews from the four health facilities in-charges were carried out. Data was analyzed using SPSS vs 25 and themes. Results: Health care provider awareness of the content of patients’ rights charter (r=0.612*, p<0.001) and practice of patient’s right charter (r=0.610*, p<0.001) were statistically significant and influenced health systems responsiveness. Conclusions: Implementation of patients’ rights charter has an influence on responsiveness of health systems. Leadership and Governance of health systems requires a structured approach to implementation of policies that positively influence responsiveness of health systems. Supervision of health care providers for best practice can provide a basis for replication in other primary care facilities and lead to achieving responsiveness of health systems.